Anchoring elements for fiber optic sensor cables: part of a system for monitoring slopes surface movements - Buras, Marcelo; Lacerda, Luiz Alkimin de; Paulino, Nayhara Arielly Pinto; Rocha, Renato Seixas da; da Silveira, Rodrigo Moraes (International Journal of Advanced Engineering Research and Science, 2020)
The fiber optic industry had a significant development from the late 80's. Besides communication, this technology is also being used for measuring a monitoring deformation, displacement, acceleration, pressure, temperature and chemical properties among others (MORIKAWA, 2004). Among the technological advantages of the use of fiber optic sensors, the most notable are: (i) sensing the possibility of several signals over a single optical fiber (multiplexing data), (ii) ease of reading of the signals (good value signal versus noise), (iii) measurements over long distances (remote sensing), (iv) immunity to electromagnetic fields, (v) absence of spark, and (vi) low weight and low material reactivity. The use of fiber optics as a tool for different kinds of geotechnical monitoring can become a highly attractive and cost effective when compared to conventional instruments such as piezometers, inclinometers, among others. A single fiber optic cable may cover a larger monitoring area compared to conventional instrumentation, and the possibility of monitoring more than one physical quantity with the same fiber optic cable. This paper covers all steps undertaken to define the size of one type of cable Anchoring Element (AE) for monitoring soil movement in natural hillslopes. To fulfill this objective laboratory tests were carried out in LACTEC, Curitiba-PR, and results and conclusions are shown in this paper.